Ankle structure of the Tokay gecko (Gekko gecko) and its role in the deployment of the subdigital adhesive system. Issue 6 (15th July 2021) - Higham, Timothy E.; Zhuang, Minga; Russell, Anthony P.
Abstract: The remarkable ability of geckos to adhere to smooth surfaces is often thought of in terms of external structures, including the branching setae that make contact with the surface producing van der Waals forces. Some geckos also exhibit unique movements of the distal segments of the limbs during locomotion and static clinging, including active digital hyperextension and considerable pedal rotation. During static clinging, geckos can exhibit considerable adduction/abduction of the pes while the crus and thigh remain firmly adpressed to the substratum. This decoupling of pedal adduction/abduction from ankle flexion/extension and pedal long‐axis rotation is a significant departure from pedal displacements of a typical lizard lacking adhesive ability. The structure of the ankle is likely key to this decoupling, although no detailed comparison of this complex joint between pad‐bearing geckos and other lizards is available. Here we compare the configuration of the mesotarsal joint of nongekkotan lizards ( Iguana and Pristidactylus ) with that of the Tokay gecko ( Gekko gecko ) using prepared skeletons, scanning electron microscopy, and micro‐computed tomographic (µCT) scans. We focus on the structure of the astragalocalcaneum and the fourth distal tarsal. The mesotarsal joint exhibits a suite of modifications that are likely associated with the secondarily symmetrical pes of pad‐bearing geckos. For example, the lateral process of the astragalocalcaneum is much more extensive in G . gecko compared with other lizards. The mesotarsal joint exhibits several other differences permitting dissociation of long‐axis rotation of the pes from flexion–extension movement, including a reduced ventral peg on the fourth distal tarsal, an articulatory pattern dominated by a well‐defined, expansive distomesial notch of the astragalocalcaneum, and an associated broad proximodorsal articulatory facet of the fourth distal tarsal. Pad‐bearing geckos are capable of effectively deploying their intricate adhesive system across a broad array of body angles because of this highly modified ankle. Future research should determine whether the differences encountered in G . gecko (and their extent) apply to the Gekkota as a whole and should examine how the elements of the ankle move dynamically during locomotion across a range of taxa. Abstract : We examined the ankle structure of pad‐bearing geckos and compared this to non‐gekkotan padless lizards. We found several major structural changes that facilitate the deployment of the adhesive system in geckos.